ChatGPT-4: dermatology aid in the emergency room - Castro, Harvey (Dermatologie (Heidelberg, Germany), 2023)
Envision a scenario in an emergency room (ER) where a clinician could capture a picture of a skin condition, subject to patient consent and adherence to privacy norms set by HIPAA and GDPR, and utilize AI, like ChatGPT‑4, to suggest differential diagnoses. Accuracy: AI could analyze vast amounts of data, potentially identifying rare conditions that a human practitioner might miss. A comparison of deep learning performance against health-care professionals in detecting diseases from medical imaging: a systematic review and meta-analysis.